Influence of bone morphological properties on a new expandable orthopaedic fastener. (March 2016) - Oldakowski, M; Oldakowska, I; Kirk, T B; Ford, C T; Sercombe, T B; Hardcastle, P; Day, R E
Abstract: Previous studies have demonstrated that bone morphological properties are a significant determinant of orthopaedic fastener fixation strength. The authors previously tested a new design of unthreaded expandable fastener (UEF) prototype against screws and demonstrated a significant increase in pull-out strength. However the effect of bone morphology on the pull-out strength of the UEF and expandable fasteners in general is unknown. This study assessed the correlation between failure force and maximum force against five microstructural parameters. The failure force of the UEF was correlated to the trabecular bone volume fraction, as with screws. Unlike screws, however, the maximum force of the UEF has an inverse relationship with cortical volume. No correlation was found between failure force and the Structural Model Index (SMI). Additionally the critical volume of interest (VOI) for the UEF is around the bottom of the fastener where the expansion occurs, whereas for the screw a full height VOI is critical. Furthermore, we observed that screw mechanical performance may be affected more by bone morphological parameters that are associated with poorer quality bone. Therefore the UEF may perform better than screws in low quality osteoporotic bone.